2001
DOI: 10.1530/eje.0.1450579
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid peroxidase antibodies during gestation are a marker for subsequent depression postpartum

Abstract: Objective: Depression is not adequately diagnosed in many cases. Therefore, the question arises as to whether markers exist for depression. We investigated whether the presence of thyroperoxidase antibodies (TPOAbs) during pregnancy can be regarded as a marker for depression in the ®rst year postpartum, particularly in relation to (overt or subclinical) thyroid dysfunction and other determinants of depression. Design: This work was a prospective observational study. Patients: A cohort of 310 unselected women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 32 publications
(21 reference statements)
4
89
1
4
Order By: Relevance
“…However, several studies have been conducted on thyroid function and postpartum depression, and the current researchers found a few studies reporting a relationship between AND and thyroid function. A recent prior publication by Kuijpens et al reported an association between TPOAb positivity and mood disturbance during pregnancy (39). In line with the current study, in studies by Koleva et of AND (42).…”
Section: Discussionsupporting
confidence: 92%
“…However, several studies have been conducted on thyroid function and postpartum depression, and the current researchers found a few studies reporting a relationship between AND and thyroid function. A recent prior publication by Kuijpens et al reported an association between TPOAb positivity and mood disturbance during pregnancy (39). In line with the current study, in studies by Koleva et of AND (42).…”
Section: Discussionsupporting
confidence: 92%
“…Because of the low prevalence of patients with a positive TPO antibody titer in our study, we could not address this hypothesis. Some indication of the importance of TPO antibodies was given by a study wherein the presence of TPO-antibodies in the first trimester of pregnancy, but not subclinical hypothyroidism per se, predicted postpartum depression (33). A recent study described that the presence of Thyroid Binding Inhibitory Immunoglobulins was related to treatment non-response in depressed patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…Positive TPOAb pregnant women have an increased risk of developing post-partum depression (22) and of giving birth to neonates that in childhood will have a lower IQ in comparison with children of mothers without TPOAb during pregnancy (23). However, it should be considered that L-T 4 treatment will not prevent depression and probably will be beneficial only in pregnant women with low serum FT 4 concentrations.…”
Section: Clinical and Laboratory Features Of Pptmentioning
confidence: 99%